Firm efficiency in selected developed and developing Asia-Pacific countries: using data envelopment analysis - Tan, Khar Mang; Kamarudin, Fakarudin; Amin Noordin, Bany Ariffin; Abdul Rahim, Norhuda (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
The paper primarily aims to examine the firm efficiency or technical efficiency (TE), pure technical efficiency (PTE) and scale efficiency (SE) in the selected developed and developing Asia-Pacific countries. The sample of this paper consists a sum of 700 firms in selected developed and developing Asia-Pacific countries over the periods from 2009-2015. The non-parametric Data Envelopment Analysis (DEA) based on the production approach is used to assess firm efficiency. On average, the results indicate that the firms in selected Asia-Pacific countries reveal the TE of 53.2per cent with input waste of 46.8per cent during the years 2009-2015. Furthermore, scale inefficiency (SIE) is the dominant source of inefficiency of firms in selected Asia-Pacific countries. The results also show that the large firms (the 350 largest firms) have exhibited higher mean TE as compared to small firms (the 350 smallest firms). Moreover, the results also shows that the large firms tend to operate at either constant return to scale (CRS) or decreasing return to scale (DRS) level. Whilst the small firms tend to operate at either CRS or increasing return to scale (IRS) level. Finally, the results also conclude that the firm in selected developed countries (300 firms) have exhibited higher mean TE than those firms in selected developing countries (400 firms) of the Asia-Pacific region.